(untitled) (Pandecta Research Law Journal, 2025)
Social transformation and the increasing economic value of land in Indonesia have intensified the demand for legal certainty in land rights. Although Law Number 5 of 1960 introduced land registration to provide legal protection through certification, the prevailing negative publication system with positive elements remains problematic. It fails to ensure state responsibility for certificate accuracy, even when acquired in good faith, thus posing risks of legal uncertainty and agrarian conflict. This study analyzes the rationale for transitioning to a pure positive publication system using Max Weber’s rational-legal bureaucracy theory, emphasizing formal procedures, predictability, and administrative accountability. Employing normative legal research with conceptual, statutory, comparative, and historical approaches, this study draws from secondary legal materials analyzed through legal interpretation and the Weberian framework. The findings reveal that a positive publication system better aligns with Weberian principles and supports legal certainty. This reform is essential for enhancing land administration legitimacy and promoting inclusive, accountable agrarian governance in Indonesia.